Analysis of flow at the vicinity of vegetation stems in the floodplain of a compound open channel. Issue 3 (2nd July 2020) - Sohrabi, Moslem; Keshavarzi, Alireza; Emdad, Homayoun; Javan, Mahmood
ABSTRACT: An analysis of flow was carried out in this study to find the effects of trees on the flow structure in a straight compound open channel. To resemble the vegetation stem, two rows of vertical rods were installed on the floodplain of an asymmetrical compound channel. Two-dimensional flow velocity was measured using Particle Image Velocimetry. The results showed a decreasing trend in turbulent kinetic energy and turbulent intensity along the floodplain. At low flow depth, a significant decrease was observed in mean velocity and kinetic energy. Similar reduction was observed at the intersection of floodplain and main channel and around the stems. Under this condition, the direction of velocity vectors changed from floodplain to the main channel. However, this trend was reversed at higher flow depths. This reversal was due to the changes in momentum transfer and shear stress at the intersection of floodplain and main channel. Additionally, a numerical analysis showed that vortices are formed at the junction of the floodplain and main channel.